The Use of the Coenzyme Q10 as a Food Supplement in the Management of Fibromyalgia: A Critical Review - Luca Campisi; Concettina La Motta (MDPI AG, 2022)
The coenzyme Q10 is a naturally occurring benzoquinone derivative widely prescribed as a food supplement for different physical conditions and pathologies. This review aims to sum up the key structural and functional characteristics of Q10, taking stock of its use in people affected by fibromyalgia. A thorough survey has been conducted, using Pubmed, Scifinder, and ClinicalTrials.gov as the reference research applications and registry database, respectively. Original articles, reviews, and editorials published within the last 15 years, as well as open clinical investigations in the field, if any, were analyzed to point out the lights and shadows of this kind of supplementation as they emerge from the literature.